Dampak COVID-19 terhadap Aktivitas Sosial Masyarakat Di Kota Lubuklinggau - Ramelia Dwi Anisa; Rusdinal Rusdinal; Firman Firman (Syntax Idea, 2021)
Coronavirus Diseases (Covid-19) is one of the many viruses that can attack humans, ranging from those without symptoms, with mild symptoms to severe symptoms. What is known is that the incubation period for Covid-19 in the human body ranges from 5-6 days and the longest incubation period is 14 days. In the current Covid-19 era, there are a lot of social activities in society that are not disturbed and cannot even be done to anticipate the spread of Covid-19 in their neighborhood. There are also community activities that have undergone changes and concerts must be carried out as a result of Covid-19. The purpose of this study was to identify the impact of Covid-19 on the social activities of the people of Lubuklinggau City. This research uses descriptive field research with qualitative research methods. The data techniques used in this study were observation, documentation and interviews and used descriptive analysis methods as data analysis techniques. The results obtained from the impact are anything that arises as a result of changes that occur in people's lives and can produce a change with a positive impact and a negative impact on the survival of the community. The results obtained in conducting research related to the impact of Covid-19 on community activities, the authors found that there are impacts that arise as a result of the existence of Covid-19, both positive and negative impacts that appear in the midst of society today